The Methuen Drama guide to contemporary American playwrights - Innes, Christopher; Middeke, Martin; Roudané, Matthew Charles; Schnierer, Peter Paul (Bloomsbury Publishing, 2018)
This is an authoritative single-volume guide to the work of 25 American playwrights from the 1960s to the present written by a team of 25 eminent scholars from the USA, Canada, Britain, Germany, and Ireland. It is the perfect companion for students of American literature and drama
Includes bibliographical references and index
Previously issued in print: 2014. Digital resource published 2018
Zielgruppe - Audience: Specialized